(untitled) (Bangladesh Journal of Zoology, 2015)
The present study was conducted to assess the prevalence and intensity of infestation by the helminth parasites in Gangetic Leaffish Nandus nandus (Hamilton, 1822) collected from different fish habitat of Savar Thana of Dhaka district in Bangladesh, during March 2013 to April 2014. A total of 80 fishes were examined and among them 51 were found infected with various helminth parasites with an infection rate of 63.75% and intensity of infection 4.53%. A total of 231 parasites was recovered from different organs of the fishes, with the highest number from the intestine. Eleven species of helminths were identified, of which three were trematodes (Clinostomum giganticum, C. complanatum, Euclinostomum multicaecum), two were cestodes (Bothriocephalus sp., Senga ophiocephalina), three were acanthocephalans (Pallisentis nandai, P. ophiocephali, Neoechinorhynchus sp,) and three were nematodes (Porrocaecum sp., Contracaecum sp., Gnathostoma spinigerum). The prevalence and intensity of parasitic infection were a bit higher in female fish than in male. The parasites were much more abundant in summer (73.33%) followed by rainy (60%) and winter (55%). The larger fishes were heavily infected (69.23%) than medium (64.71%) and smaller (50%) fishes Bangladesh J. Zool. 42(2): 183-190, 2014